Disturbance of Arginase Activity and Nitric Oxide Levels in Iraqi Type 2 Diabetes Mellitus (Baghdad Science Journal, 2018)
This study is an attempt to find whether arginine metabolism dysregulation by arginase activity is related to hyperglycemia, followed by changes in nitric oxide (NO) generation in type 2 diabetic patients. This study includes 42 control subjects (Group I), and 92 Iraqi patients with type 2 diabetes mellitus (T2DM). The patient group was subdivided into two groups: Group II (54) with T2DM only and Group III (38) with T2DM and dyslipidemia (who were treating with atorvastatin along with diabetes treatment). The samples were obtained to measure arginase activity and NO levels. Serum arginase activity increased significantly in patients(groupII and groupIII) compared to control group. While serum NO level was significantly lower in diabetic patients as compared to control group, three significant correlations appeared in this study between glucose and arginase activity, glucose and NO levels, and between arginase activity and NO levels. The results also show that treatment with atorvastatin affects arginase activity and NO levels. Increasing in levels of arginase activity can be considered as an indicator of diabetic status. Endothelial dysfunctions accompanied with diabetes mellitus reverses correlation between arginase and NO in diabetic